The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1111/jsm.12002
|View full text |Cite
|
Sign up to set email alerts
|

The Physical Consequences of Gynecologic Cancer Surgery and Their Impact on Sexual, Emotional, and Quality of Life Issues

Abstract: Introduction Surgical management of gynecologic cancer can cause short- and long-term effects on sexuality, reproductive function, and overall quality of life (QOL) (e.g., sexual dysfunction, infertility, lymphedema). However, innovative approaches developed over the past several decades have improved oncologic outcomes and reduced treatment sequelae. Aim To provide an overview of the standards of care and major advancements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
63
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(67 citation statements)
references
References 174 publications
(208 reference statements)
2
63
0
1
Order By: Relevance
“…Standardization also helps measure the magnitude of expected versus observed sexual functioning. Clinically, using any sexual functioning measure may help patients and/or providers initiate questions about sexual function and improve their communication about sexual functioning (Carter, Stabile, Gunn, & Sonoda, 2013; Dizon, Suzin, & McIlvenna, 2014). Elsewhere, with men treated for prostate cancer, help seeking behaviors for sexual dysfunction appears to be directly related to cancer stage and severity of dysfunction (Schover, Fouladi, Warneke, et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Standardization also helps measure the magnitude of expected versus observed sexual functioning. Clinically, using any sexual functioning measure may help patients and/or providers initiate questions about sexual function and improve their communication about sexual functioning (Carter, Stabile, Gunn, & Sonoda, 2013; Dizon, Suzin, & McIlvenna, 2014). Elsewhere, with men treated for prostate cancer, help seeking behaviors for sexual dysfunction appears to be directly related to cancer stage and severity of dysfunction (Schover, Fouladi, Warneke, et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…1,9Y12 Most women diagnosed with GC are elderly and postmenopausal; however, previous studies have also shown that elderly patients continue sexual relationships after diagnosis of cancer if possible. 13,14 Sexuality should therefore be addressed as a central topic during consultation of all patients. 15 Ekwall et al observed that openness and communication about sexual issues is often lacking.…”
mentioning
confidence: 99%
“…Womens' perceived causes of diseases may increase their risk for anxiety. Communication between the patient and clinician about sexual issues offers the health care professional the ability to understand a patient's concerns and offer appropriate treatments (Audette and Waterman, 2010;Carter et al, 2013).…”
Section: Discussionmentioning
confidence: 99%